Experimental study of the physicochemical structure and moisture readsorption characteristics of Zhaotong lignite after hydrothermal and thermal upgrading. (1st December 2016) - Feng, Xiaofei; Zhang, Cheng; Tan, Peng; Zhang, Xiaopei; Fang, Qingyan; Chen, Gang
Highlights: Typical Chinese lignite was upgraded hydrothermally and thermally to study the moisture readsorption characteristic. Different upgrading method has different function for the removal of oxygen-containing functional groups in lignite. Evolution mechanisms of pore structure by temperature and pressure during upgrading were obtained. A moisture readsorption model was established with changes of the physical and chemical structure. Abstract: Hydrothermal and thermal upgrading techniques are promising coal drying methods that enable the utilization of low rank coals. In this study, Zhaotong (ZT) lignite from the Yunnan province of China was hydrothermally upgraded at 150–300 °C and thermally upgraded at 200–500 °C; then, the correlation between the changes in the physical and chemical structures and the moisture readsorption characteristics were investigated. The maturity of lignite was improved by the upgrading treatment. The main hydrophilic oxygen-containing groups, including hydroxyl and carboxyl, were effectively removed as the upgrading temperature increased. In addition, the removal of hydroxyl groups was more remarkable during hydrothermal upgrading. Irreversible changes occurred in the pore structure of the treated lignites; the specific surface area and total pore volume first increased and then decreased with hydrothermal upgrading, whereas the specific surface area and total pore volume continually increased with thermal upgrading as the temperature increased. In addition, the gel-like structure of the lignite experienced violent shrinkages and collapses. The moisture readsorption performance was effectively inhibited under the synergy effects of the physicochemical structure such that the moisture readsorption ratio ( MRR ) and moisture holding capacity (MHC) decreased continuously with the increasing upgrading temperature. An MHC model built through multiple linear regressions proved suitable to describe the moisture readsorption of the upgraded lignites.